Non-darcy porous media flow in no-slip and slip regimes - Miguel, A. F. (2012)
In this paper lattice-Boltzmann equation method is used to simulate non-Darcy flow in porous media. 2-D in-line and staggered arrangements of uniform cylin-ders have been considered. The results of a comprehensive computational evaluation are reported: the range of validity of Darcy-Forchheimer equation is investigated and correlations for macroscopic transport properties are presented (i. e., for the permeability and the inertial parameter). Our investigation covers both no-slip and the slip-flow regimes.